DIASPORA INVOLVEMENT IN INSURGENCIES: INSIGHTS FROM THE KHALISTAN AND TAMIL EELAM MOVEMENTS - C. Christine Fair (Nationalism and Ethnic Politics, 11:125-156, 2005, 2005)
This article exposits and contrasts the roles of two diasporas in ethnic conflict waged in their homelands, namely the Sikh diaspora's involvement in the Punjab insurgency in north India and the Sri Lankan Tamil diaspora's role in Sri Lanka's Tamil insurgency. It draws out the various similarities and distinctions between the two in their use of technology, means of mobilization and identity production, and the geographical and political reach of their institutional arrangements.The article argues that the varying means by which these diasporas came into being affected the ways in which they mobilized and the positions they espoused towards homeland politics. It finds that the abilities of the two diasporas to contribute to events "back home" differed in part because of the scope of their respective institutional arrangements.